Africa's health challenges sovereignty, mobility of people and healthcare governance - edited by Andrew F. Cooper (Burlington Ashgate, 2013)
Africa's health challenges : sovereignty, mobility of people and healthcare governance
Includes bibliographical references (pages [215]-243) and index.
Keywords: Public health--Africa.